ISLAMISASI PENDIDIKAN (Kewajiban Agama, Kebutuhan Sosial, dan Kepentingan Pendidikan) - Dahniar Dahniar (AZKIA : Jurnal Aktualisasi Pendidikan Islam, 2019)
Since the idea of ​​Islamization of science was initiated by Muslim scholars a few years ago both through the Seminar and through various papers and writings, various responses to it began to emerge, both those who supported and refused, the efforts to realize them were slowly becoming more prevalent and several related works with the idea of ​​Islamization emerging in the Islamic world. For example economic Islamization, Islamic Islamization, Islamization of science and so on. The basic term and the description of Islamization have different meanings and explanations. For example in the case of medicine, the emergence of the thoughts of Muslim scholars in medical studies, there are some opinions that are well-known in Muslim medical circles that; science is not absolute in the sense that it not only infuses knowledge, but also instills value which both have a close relationship.